Non‐Market Strategies and Credit Benefits: Unpacking Heterogeneous Political Connections in Response to Government Anti‐Corruption Initiatives - Fengyan, Yu; Hongjuan, Zhang; Tan, Justin; Qi, Liang (Journal of Management Studies, 2022)
Abstract This paper explores how political connections influence firms’ credit benefits, especially when the political environment improves. The authors distinguish two types of political connections – connections to government officials and connections to council deputies – according to whether the political benefits they provide are exclusive and definite. Employing a panel data set comprised of Chinese listed firms’ bank‐loan contracts from 2008 to 2014, they find politically connected firms – and particularly firms with connections to government officials – enjoy significantly lower loan costs than their non‐connected counterparts. Moreover, they find that anti‐corruption efforts, which reflect improvement in the political environment, reduce the credit benefits of political connections, but only for firms that have connections to government officials. Results emphasize the value of unpacking the heterogeneity of political connections and illuminate the importance of more complete assessment of corporate political strategies in changing political environments.